Removal of Ni and Cd cations from wastewater using photocatalytic reactions: Review paper - Al-Hamadani, Amal J. M.; Al-Mamoori, Ahmed A.; Al-Naseri, Hayder (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
A clean environment and human health depend on removing heavy metal ions from wastewater. Ecosystems and public health are seriously threatened by heavy metal ions, such as nickel (Ni), lead (Pb), cadmium (Cd), vanadium (V), chromium (Cr), and copper (Cu). For example, because of its toxic effects, cadmium is only permitted at 0.005 mg/L in drinking water, while lead has a maximum permissible concentration of 0.015 mg/L. Heavy metal ions have been extracted from various wastewater types using methods such as adsorption, membrane filtration, chemical addition, electrochemical treatment, and photocatalysis. Nevertheless, conventional techniques frequently encounter obstacles like exorbitant operating expenses and restricted effectiveness, with removal rates occasionally falling below 70%. These techniques can also result in hazardous byproducts, which makes wastewater treatment procedures more difficult. Because photocatalysis is so versatile in environmental remediation, it can be used to remove heavy metals. The ability of semiconductor nanostructures based on metal oxides to effectively remove heavy metals from contaminated water has garnered attention recently. For instance, when exposed to particular light wavelengths, zinc oxide (ZnO) and titanium dioxide (TiO2) can remove some heavy metals with up to 95% removal efficiencies. Zeolites have been used increasingly in wastewater treatment over the past 20 years; applications have shown removal capacities of up to 100 mg/g for cadmium and 150 mg/g for lead. This article examines recent developments in using zeolites to extract heavy metals from contaminated solutions. Both traditional and modern wastewater treatment methods are compiled and discussed in this comprehensive analysis, including the application of ZSM-5 zeolites in photocatalytic technology, which can lower operating costs by up to 30% and improve removal efficiencies. Combining zeolites with photocatalytic systems is a viable strategy to raise the efficacy of heavy metal remediation in wastewater treatment.